The effectiveness of core stabilization exercise in adolescent idiopathic scoliosis: A randomized controlled trial. (June 2017) - Gür, Gözde; Ayhan, Cigdem; Yakut, Yavuz
Background: Core stabilization training is used to improve postural balance in musculoskeletal problems. Objectives: The purpose of this study was to investigate the effectiveness of stabilization training in adolescent idiopathic scoliosis. Study design: A randomized controlled trial, pretest–posttest design. Methods: In total, 25 subjects with adolescent idiopathic scoliosis were randomly divided into two groups: stabilization group ( n = 12) and control group ( n = 13). The stabilization group received core stabilization in addition to traditional rehabilitation, and the control group received traditional rehabilitation for 10 weeks. Assessment included Cobb's angle on radiograph, apical vertebral rotation in Adam's test, trunk asymmetry (Posterior Trunk Symmetry Index), cosmetic trunk deformity (Trunk Appearance Perception Scale), and quality of life (Scoliosis Research Society-22 questionnaire). Results: Inter-group comparisons showed significantly greater improvements in the mean change in lumbar apical vertebral rotation degree and the pain domain of Scoliosis Research Society-22 in the stabilization group than those in the control group ( p < 0.05). No significant differences were observed for other measurements between the groups; however, trends toward greater improvement were observed in the stabilization group. Conclusion: Core stabilization training in addition to traditional exercises was more effective than traditional exercises alone in the correction of vertebral rotation and reduction of pain in adolescent idiopathic scoliosis. Clinical relevance: Stabilization exercises are more effective in reducing rotation deformity and pain than traditional exercises in the conservative rehabilitation of adolescent idiopathic scoliosis. These improvements suggest that stabilization training should be added to rehabilitation programs in adolescent idiopathic scoliosis.